Reaktualisasi Nilai-Nilai Keislaman Untuk Membangun Karakter Bangsa - Idzan Fautanu (Al-Risalah, 2011)
The major citizens of Indonesia are Muslim, and even the biggest in the world. However, the phenomenon of conflict on behalf of religions and ethnics which resulted violence has been a big concern for this country. To solve that problem, we need to build the nation‐character of the Indonesians so that they have the sense‐ofnationalism. The question is how can the Islamic and Indonesian values build the nation‐character? Basically, the nation‐character can be established through moral value. This establishment can be built by two aspects: autonomy (education) and heteronomy (environment). Besides that, the empowerment of Indonesian values and views, which are the result of cultural and religion Islamic values, we need to establish and develop the characters from several aspects: physical, spiritual, emotional, and intellectual. The application of Indonesian and Islamic values will hopefully build effective and high nation‐characters.